Water quality, human health risk, and pesticides accumulation in African catfish and Nile tilapia from the Kitchener Drain-Egypt - Ahmed A. Metwally; Malik M. Khalafallah; Mahmoud A. O. Dawood (Scientific Reports, 2023)
Abstract Pesticides are toxic and could negatively impact humans and the ecosystem. The Kitchener Drain is among the longest drains in Egypt and carries a wide range of wastewater from the agriculture sector, which contains pesticides and may pollute the ecosystem. Thus, water quality, human health risk, and pesticide accumulation in African catfish and Nile tilapia from the Kitchener Drain-Egypt. The water and fish samples were collected from Kitchener Drain in Kafr Elsheikh Governorate, Egypt, during the four seasons. The results indicated that heptachlor and diazinon were undetected during the four seasons. However, endosulfan, chlorpyrifos, and dicofol were detected in winter and autumn. Only p,p′-DDT was detected during spring. Endosulfan, heptachlor, and aldrin were detected in Nile tilapia during winter. Only heptachlor and aldrin were detected during spring. Endosulfan, heptachlor, dicofol, p,p′-DDT, chlorpyrifos, and diazinon were detected in the autumn season. In summer, dicofol and p,p′-DDT were detected, while endosulfan, heptachlor p,p′-DDT, aldrin, chlorpyrifos, and diazinon were not detected. In African catfish, endosulfan, heptachlor, dicofol, and p,p′-DDT were detected during winter, while chlorpyrifos, aldrin, and chlorpyrifos, aldrin, and diazinon were not detected. In the spring season, endosulfan, heptachlor, and aldrin were detected. Endosulfan, heptachlor, dicofol, p,p′-DDT, aldrin, chlorpyrifos, and diazinon were detected in the autumn season. Similarly, in the summer season, endosulfan, heptachlor, dicofol, p,p′-DDT, aldrin, chlorpyrifos, and diazinon were detected. The sequence of estimated daily intake (EDI) in Nile tilapia during the four seasons is heptachlor > endosulfan > dicofol > p,p′-DDT > aldrin > diazinon > chlorpyrifos. The sequence of EDI in African catfish during the four seasons is endosulfan > p,p′-DDT > heptachlor > aldrin > dicofol > diazinon > chlorpyrifos. In conclusion, the results confirmed the absence of a hazard index for consuming Nile tilapia and African catfish collected from the Kitchener drain.